FORS2 HIT mode: Phase resolved spectroscopy of RXJ0806.3+1527 - Mason, E; Israel, G; O'Brien, K (2008)
A 321s modulation was discovered in 1999 in the X-ray light curve of RXJ0806.3+1527, but it was only in 2002, thanks to VLT photometric and spectroscopic observations that its likely nature was unveiled. The optical spectrum of RXJ0806.3+1527 showed a blue continuum, no intrinsic absorptions but just broad (FWHM∼1500km/s) low equivalent width (EW∼1-6A) emission lines, which were identified with the HeII Pickering series. HeII emissions are characteristics of X-ray poor AM CVn systems, i.e. double degenerate binaries hosting two white dwarfs. If such, RXJ0806.3+1527 represents the shortest orbital period binary discovered ever. Recently, we carried out the first 321s period phase resolved spectroscopic study by means of the VLT FORS2 HIT mode. The program was aimed at studying the orbital motion of the two components by following the shape, centroid and intensity of the HeII lines through the orbit. Here, we report the preliminary results. © 2008 American Institute of Physics.